Public investment, private investment, governance and tourism growth in five South Asian Association for Regional Cooperation countries - Nawaz, Muhammad Atif (2018)
The present research investigates the effects of public and private investment in Travel and Tourism (T&T), and their interaction effect on tourism growth in five South Asian Association for Regional Cooperation (SAARC) countries. It also examines the interaction effect of public and private investment with governance on tourism growth in the region. The panel data for the five SAARC countries, from 1996 to 2015, is analyzed using Fully Modified Ordinary Least Squares and Pooled Mean Group methods. The study findings reveal that public investment, private investments, and their interaction positively affect tourism growth. The interaction effects of governance with public and private investments produce mixed results for the three indicators of governance. The interaction of political stability and absence of violence with private investment shows positive effect, however, its interaction with public investment illustrates negative effect on tourism growth. In addition, the interaction effect of control of corruption and public investment on tourism growth is positive, while there is an evidence of negative effect of the interaction of control of corruption and private investment. Similarly, the interaction effect of rule of law and public investment on tourism growth is positive, whereas, it is negative in case of the interaction of rule of law and private investment. Therefore, it is recommended that public investment needs to be increased in T&T, in addition to ensure conducive environment for private sector participation in order to reap its full potential. The study also suggests improving the governance, as it enhances the efficiency and productivity of public and private investments in T&T.